2019
DOI: 10.1093/ntr/ntz015
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Belief That Organic and Additive-Free Tobacco Products are Less Harmful Than Regular Tobacco Products: Results From the 2017 US Health Information National Trends Survey

Abstract: Significance US smokers of Natural American Spirit, a brand marketed as “organic” and “additive-free,” are more likely than other cigarette smokers to believe that their brand might be less harmful than other brands. This article (1) describes the prevalence of belief that “organic” and “additive-free” tobacco is less harmful than regular tobacco products in the US population and (2) describes the sociodemographic characteristics of adults who believe tobacco products with these descriptors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…These descriptions are strikingly similar to terms used to market American Spirit cigarettes as 'additive free', 'natural' or 'simple'. [24][25][26] Use of these descriptors effectively constructed a comparative health halo around American Spirit versus other cigarettes [26][27][28][29][30] and led to the FDA requirement that 'additive free' and 'natural' be removed from American Spirit marketing. 31 It is possible that the presence of analogous terminology in oral nicotine marketing could suggest products are healthier and lower risk to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…These descriptions are strikingly similar to terms used to market American Spirit cigarettes as 'additive free', 'natural' or 'simple'. [24][25][26] Use of these descriptors effectively constructed a comparative health halo around American Spirit versus other cigarettes [26][27][28][29][30] and led to the FDA requirement that 'additive free' and 'natural' be removed from American Spirit marketing. 31 It is possible that the presence of analogous terminology in oral nicotine marketing could suggest products are healthier and lower risk to consumers.…”
Section: Discussionmentioning
confidence: 99%
“…In cities with lower smoking prevalence, harm perceptions of smoking are likely greater, and smoking is less normative (Huang et al, 2014;Kang and Cho, 2020). Popularity of NAS, which is often perceived as a safer smoke (Pearson et al, 2019;Leas et al, 2017), may deter cities' efforts to further reduce smoking prevalence. Future research should examine whether NAS sales increase as smoking prevalence declines and to what extent industry advertising contributes to increased sales.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that smokers and nonsmokers perceive NAS as less harmful to health than other cigarettes (O'Connor et al, 2017). Belief in reduced harm of "natural," "organic," or "additive-free" cigarettes compared to other cigarettes is widespread among American adults (Pearson et al, 2019; https://doi.org/10.1016/j.addbeh.2020.106558 Received 14 May 2020; Received in revised form 23 June 2020; Accepted 12 July 2020 T 2017). In experimental studies, both smokers and non-smokers exposed to NAS advertising (Baig et al, 2019;Gratale et al, 2018) and packaging rated the brand as less harmful for health (Baig et al, 2019;Gratale et al, 2018; and the environment (Gratale et al, 2018; relative to other brands not promoted as "natural."…”
Section: Introductionmentioning
confidence: 99%
“…For instance, research has shown that packaging color, a “healthier” look and an organic label influence perceptions of food healthfulness, and such perceptions can extend to other types of organic products [17,18,19]. Research regarding natural cigarettes has tied the use of the word “natural” in ads or on packs to misbeliefs, as packs labeled natural, organic or additive-free are erroneously perceived as less harmful [9,10,20,21], especially among vulnerable groups including youth [22,23]. Analysis of NAS marketing has further supported these findings [24,25,26], showing that implicitly communicated misperceptions about NAS healthfulness influence intentions to use NAS [8,27].…”
Section: Introductionmentioning
confidence: 99%